Dynamic Curvature Nanochannel‐Based Membrane with Anomalous Ionic Transport Behaviors and Reversible Rectification Switch. Issue 11 (11th January 2019) - Wang, Miao; Meng, Haiqiang; Wang, Dan; Yin, Yajun; Stroeve, Pieter; Zhang, Yunmao; Sheng, Zhizhi; Chen, Baiyi; Zhan, Kan; Hou, Xu
Abstract: Biological nanochannels control the movements of different ions through cell membranes depending on not only those channels' static inherent configurations, structures, inner surface's physicochemical properties but also their dynamic shape changes, which are required in various essential functions of life processes. Inspired by ion channels, many artificial nanochannel‐based membranes for nanofluidics and biosensing applications have been developed to regulate ionic transport behaviors by using the functional molecular modifications at the inner surface of nanochannel to achieve a stimuli‐responsive layer. Here, the concept of a dynamic nanochannel system is further developed, which is a new way to regulate ion transport in nanochannels by using the dynamic change in the curvature of channels to adjust ionic rectification in real time. The dynamic curvature nanochannel‐based membrane displays the advanced features of the anomalous effect of voltage, concentration, and ionic size for applying simultaneous control over the curvature‐tunable asymmetric and reversible ionic rectification switching properties. This dynamic approach can be used to build smart nanochannel‐based systems, which have strong implications for flexible nanofluidics, ionic rectifiers, and power generators. Abstract : Dynamic shape changes in biological nanochannels play a vital role in the implementation of various significant functions in life processes. In this work, the concept of a dynamic nanochannel system is developed, which is a new way to regulate ion transport in nanochannels by using the dynamic change of the curvature of channels to adjust ionic rectification in real time.